2001
DOI: 10.1016/s0896-6273(01)00481-0
|View full text |Cite
|
Sign up to set email alerts
|

Population Coding of Stimulus Location in Rat Somatosensory Cortex

Abstract: This study explores the nature of population coding in sensory cortex by applying information theoretic analyses to neuron pairs recorded simultaneously from rat barrel cortex. We quantified the roles of individual spikes and spike patterns in encoding whisker stimulus location. 82%-85% of the total information was contained in the timing of individual spikes: first spike time was particularly crucial. Spike patterns within neurons accounted for the remaining 15%-18%. Neuron pairs located in the same barrel co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
161
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(181 citation statements)
references
References 52 publications
19
161
1
Order By: Relevance
“…Here we solidify this identification by showing that ⌬I is a rigorous upper bound on the information loss. This result is useful because it allows us to interpret the spate of recent experiments in which ⌬I/I was found to be on the order of 10% or less (Nirenberg et al, 2001;Petersen et al, 2001Petersen et al, , 2002Panzeri et al, 2002b;Pola et al, 2003): in those experiments, one could ignore correlations when decoding and lose at most ϳ10% of the information.…”
Section: Redundancy Reductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Here we solidify this identification by showing that ⌬I is a rigorous upper bound on the information loss. This result is useful because it allows us to interpret the spate of recent experiments in which ⌬I/I was found to be on the order of 10% or less (Nirenberg et al, 2001;Petersen et al, 2001Petersen et al, , 2002Panzeri et al, 2002b;Pola et al, 2003): in those experiments, one could ignore correlations when decoding and lose at most ϳ10% of the information.…”
Section: Redundancy Reductionmentioning
confidence: 92%
“…Several authors (Eckhorn et al, 1988;Meister et al, 1995;Vaadia et al, 1995;deCharms and Merzenich, 1996;Dan et al, 1998;Steinmetz et al, 2000) have suggested that they are, whereas others (Nirenberg et al, 2001;Oram et al, 2001;Petersen et al, 2001;Levine et al, 2002;Panzeri et al, 2002a,b;Averbeck and Lee, 2003;Golledge et al, 2003) have argued that they are not or that they play a minor role. The debate has arisen in large part because different methods have been used to assess the role of correlations, and different methods yield different answers.…”
Section: Introductionmentioning
confidence: 99%
“…Although ⌬I shuff led cannot be used to assess directly the role of correlations in decoding information, it can be used to provide information about how correlations affect the transformation from stimulus to response (21,31,33). In particular, the quantity ⌬I shuff led Ϫ ⌬I is especially useful for understanding the relation between signal and noise correlations (21).…”
Section: Other Measures Of the Importance Of Correlationsmentioning
confidence: 99%
“…However, most studies quantifying first-spike latency information assume that the brain has an independent reference for stimulus onset from which to extract latency. In the majority of situations, this independent onset reference does not exist; the need for a timing reference has caused some to question the ultimate feasibility of first-spike latency codes (8).A number of authors have suggested possible alternative latency measures (1,3,5,6), but few have actually compared the information contained in different onset references. Stecker and Middlebrooks (9) computed the information contained in the relative spike timing of pairs of simultaneously recorded neurons in auditory cortex, and Furukawa et al (10) compared the median errors from neural-network estimates of location with similar data.…”
mentioning
confidence: 99%
“…A number of authors have suggested possible alternative latency measures (1,3,5,6), but few have actually compared the information contained in different onset references. Stecker and Middlebrooks (9) computed the information contained in the relative spike timing of pairs of simultaneously recorded neurons in auditory cortex, and Furukawa et al (10) compared the median errors from neural-network estimates of location with similar data.…”
mentioning
confidence: 99%